2023
DOI: 10.1097/sap.0000000000001431
|View full text |Cite
|
Sign up to set email alerts
|

Venous Anastomoses in Anterolateral Thigh Flaps for the Lower Extremity

Abstract: BackgroundDual venous drainage for anterolateral thigh flaps has been proposed to protect against flap-related complications in head and neck applications. Here we report our experience with single vs dual venous anastomosis during lower extremity free-tissue transfer.MethodsAll free anterolateral thigh flaps for lower extremity reconstruction from 2011 to 2017 were retrospectively reviewed. An algorithm was used to determine the type and number of venous anastomoses, emphasizing patient anatomy, venous qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 26 publications
1
17
0
Order By: Relevance
“…Reconstruction of traumatic injuries was described in two studies (29%) (Stranix et al, 2016; 2018). Four studies (57%) described mixed etiology wounds (Heidekrueger et al, 2016; Khan et al, 2020; Lorenzo et al, 2011; Mattos et al, 2018), and a single study (14%) did not specify the type of lower limb injury/wound (Hallock, 2000).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reconstruction of traumatic injuries was described in two studies (29%) (Stranix et al, 2016; 2018). Four studies (57%) described mixed etiology wounds (Heidekrueger et al, 2016; Khan et al, 2020; Lorenzo et al, 2011; Mattos et al, 2018), and a single study (14%) did not specify the type of lower limb injury/wound (Hallock, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…One proposed method to reduce venous congestion is the addition of a secondary vein (Hallock, 2000; Lorenzo et al, 2011; Matthews et al, 2018; Stranix et al, 2016; 2018). Secondary venous anastomosis is thought to decrease venous resistance and therefore maintain venous flow at lower pressure gradients (Mattos et al, 2018; Stranix et al, 2016). Additionally, a secondary anastomosis provides alternative drainage in the case when the primary outflow tract is obstructed (Stranix et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…After the first exclusion, researchers reviewed full-texts for the remaining 10 studies. Finally, eight articles [16][17][18][19][20][21][22][23] with a total of 1,434 flaps were included in the systematic review (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Further, Lorenzo et al [22] found that using the deep vein system is more important than using two vein anastomosis, and also reported more partial flap loss for two vein anastomosis. Mattos et al [18] also insisted that using the deep venous system is more important than using double venous anastomosis technique. However, Stranix et al [19] showed that dual venous anastomosis had protective effects against flap failure.…”
Section: Discussionmentioning
confidence: 99%
“…However, in settings of critical limb ischemia or compromised in-flow an end to side anastomosis was performed. We have previously studied an algorithm for venous anastomosis and preferentially utilize the deep venous system, avoiding refluxing veins and matching for size [8] .…”
Section: Methodsmentioning
confidence: 99%